PENGARUH SENAM TERA TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA YANG MENGALAMI HIPERTENSI DI PUSKESMAS DELI TUA TAHUN 2025 - manik, maria hermita; Samura, M. Dasril (Jurnal Penelitian Keperawatan Medik, 2025)
Hypertension is a common health problem among the elderly and poses a risk of serious complications such as cardiovascular diseases. The management of hypertension is not only carried out pharmacologically but also through non-pharmacological interventions, one of which is Tera Exercise. Tera Exercise is a physical activity believed to be effective in reducing blood pressure through mechanisms of relaxation, stress management, and improved blood circulation. This study aimed to analyze the effect of Tera Exercise on blood pressure reduction in elderly individuals with hypertension at Puskesmas Deli Tua in 2025. This study employed a quasi-experimental design with a One Group Pretest-Posttest Design. The sample consisted of 23 elderly individuals selected using purposive sampling. Systolic and diastolic blood pressure were measured before and after the intervention using a digital sphygmomanometer. Data were analyzed using the Wilcoxon test to examine differences in blood pressure before and after the intervention. The results showed a significant reduction in blood pressure after the implementation of Tera Exercise (p = 0.001), (p < 0.05). The average reduction in systolic blood pressure was 11.051 mmHg, while the average reduction in diastolic blood pressure was 11 mmHg. These findings indicate that Tera Exercise is effective in lowering blood pressure in elderly individuals with hypertension. Tera Exercise can be recommended as a safe and easy-to-perform non-pharmacological intervention to help manage blood pressure in the elderly. This intervention is expected to be routinely implemented to improve the quality of life of elderly individuals.